Legal Protection For Housing Consumers Who Suffer Losses Due to Fictitious Land Sales: Abstract, INTRODUCTION, METHODS, DISCUSSION, CONCLUSION, BIBLIOGRAPHY - Aprilianti, Viona; Kirana, Cindy Asya; Ardiansyah, Ferdi; Marlina, Tina; Handiriono, Raden (Ann Publisher, 2024)
Fictitious sales are practices that harm consumers and violate their rights, which have been protected and guaranteed by law. One of the cases that emerged was the sale of fake land by PT X in the Arjawinangun area, which caused losses for many consumers. This study examines the legal protection for consumers harmed by the sale of fake land and the legal steps taken by consumers for those who suffer losses due to the sale of counterfeit land. Normative juridical is the research method used in this study, which involves the study of regulations related to consumer legal protection and analyzing legal documents, including consumer protection laws. The research data was obtained from secondary data, namely the decision of the Cirebon District Court, using a data collection method through literature studies. The analysis shows that consumers have rights protected by law, including the right to be compensated for their losses. This study concludes that a law on consumer protection fosters consumers who are harmed by counterfeit sales; the law guarantees the right of consumers to receive correct information and prohibits the sale of goods and services that are not under the agreement. BPSK has to resolve disputes between consumers and perpetrators, where consumers can also file a lawsuit in the district court if fake sales harm them.